1995
DOI: 10.1155/dte.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Trichophytobezoar Without Gastrointestinal Complaints

Abstract: Gastrointestinal complaints may be the presenting symptoms of trichophytobezoar. We report a patient, who had an epigastric lump and enlarged lymph nodes on the left side of the neck, but without any gastrointestinal complaint. The clinical diagnosis suggested lymphoma or gastric cancer with secondary masses in the cervical lymph nodes. The diagnosis ultimately proved to be tubercular lymphadenitis on biopsy and gastric trichophytobezoar on endoscopy and laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Bezoars can be asymptomatic or patients can present with various nonspecific gastrointestinal symptoms. [ 16 ] Abdominal ultrasonography, computed tomography, gastrointestinal radiography, and endoscopy are useful for detecting bezoars. Among these diagnostic methods, endoscopic examination plays the greatest role in making a definitive diagnosis of the composition of gastrointestinal bezoars, as well as in determining their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bezoars can be asymptomatic or patients can present with various nonspecific gastrointestinal symptoms. [ 16 ] Abdominal ultrasonography, computed tomography, gastrointestinal radiography, and endoscopy are useful for detecting bezoars. Among these diagnostic methods, endoscopic examination plays the greatest role in making a definitive diagnosis of the composition of gastrointestinal bezoars, as well as in determining their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Retrieval results showed that only 8 articles on human trichophytobezoar were reported. Of these articles, Scorpio and Sharma [ 5 ] reported a 5-year-old girl with large terminal ileal trichophytobezoar causing perforation peritonitis, Ciampa et al [ 6 ] reported a case of a 13-year-old girl with a 19 × 11 × 2-cm 3 trichophytobezoar, Malik et al [ 16 ] reported a case of trichophytobezoar without gastrointestinal complaints in a 42-year-old woman, Lee et al [ 22 ] reported a 73-year-old male with gastric cancer and trichophytobezoar, and Capeche et al [ 23 ] reported a 20 years old man with duodenal trichophytobezoar. All of these cases were treated with laparotomy.…”
Section: Discussionmentioning
confidence: 99%